2014
DOI: 10.1063/1.4896285
|View full text |Cite
|
Sign up to set email alerts
|

Using dual-band asymmetric transmission effect of 2D metamaterial to manipulate linear polarization state of electromagnetic waves

Abstract: This work demonstrates a two-dimensional (2D) bilayered metamaterial that exhibits dual-band asymmetric transmission (AT) effect for linear polarization. The measured cross-polarization transmissions are 0.88 at 5.68 GHz and 0.92 at 10.7 GHz in one direction, while the corresponding cross-polarization transmissions are suppressed down to 0.17 and 0.18 in the opposite direction, and the AT parameters Δx/Δy reach 0.73/−0.73 and 0.80/−0.80 respectively. The simulated surface current distributions reveal that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In [11] and [12], two kinds of metamaterials to achieve asymmetric transmission of the EW with linear polarization are…”
Section: A Design Of the Pcm Unit Cellmentioning
confidence: 99%
“…In [11] and [12], two kinds of metamaterials to achieve asymmetric transmission of the EW with linear polarization are…”
Section: A Design Of the Pcm Unit Cellmentioning
confidence: 99%
“…Since the unit cells of CMMs have no mirror symmetry, a cross-coupling effect of the electric or magnetic field on the transmitted electromagnetic wave will emerge. Therefore, asymmetric transmission (AT) [12][13][14][15][16][17][18] and polarization conversion [19][20][21][22] can be realized due to the cross-coupling effect.…”
mentioning
confidence: 99%
“…Intuitively, the nonreciprocal transmission in this effect seems to be wrong; indeed, it strictly obeys Lorentz's reciprocity theorem. Previous studies have shown that the AT phenomenon can be acquired through circularly 16,17) and linearly polarized electromagnetic waves in asymmetrically spilt rings, 16,24) chiral L-shaped metastructures, 18) four U-shaped split ring resonators, 19) and twisted split ring resonators. 20) In addition, L-shaped CMMs have also been employed to realize the AT effect.…”
mentioning
confidence: 99%
“…AT devices related to polarization are also used in devices such as polarization converters, class diodes and photodiodes 28 , 29 . At present, researchers use artificial structures such as metamaterials 30 32 to design AT devices without an applied magnetic field, which are compact and more conducive to integration, and have been widely studied in microwave, near-infrared, and optical wavelength bands. MS lens or transmitarrays with ultra-low profile and flat plate features play an extremely important role in wireless communications systems.…”
Section: Introductionmentioning
confidence: 99%